Judicial Citations - an Empirical Study of Citation Practice in the New Zealand Court of Appeal - Smyth, Russell (Victoria University of Wellington Law Review, 2000)
In this article, the author examines citations to case law and secondary authorities in a sample of 300 cases in the New Zealand Court of Appeal decided between 1995 and 1999. The author discusses the rationale for citing authorities and considers the citation practice of the Court of Appeal as well as of individual judges. Comparisons are also drawn with previous studies of overseas' courts citation practices.